MODERASI BERAGAMA DI INDONESIA: Kajian Tentang Toleransi Dan Pluralitas Di Indonesia - Juli Santoso; Timotius Bakti Sarono; Sutrisno Sutrisno; Bobby Kurnia Putrawan (Sekolah Tinggi Teologi Berita Hidup, 2022)
The reality of progress which is the wealth of the nation has been misinterpreted by religious groups that divide the nation. The reality today is that religion has become a commodity that exploits